Ḥajj Health Management in Dutch East Indie under Ordonantie van 1922 - Wahyudhi, Johan; Madjid, M. Dien; Subchi, Imam (AHKAM : Jurnal Ilmu Syariah, 2024)
This article discusses the handling of the health of pilgrims since the Ordonantie van 1922, which regulates the organization of the ḥajj in the Dutch East Indies. As is known, during this period, there were several epidemics, such as smallpox, cholera, and the Spanish flu. Governments from around the world agreed to prevent the spread of the outbreak by cooperating in the health sector. This study uses historical research methods, which are based on four activities, starting from finding sources, criticizing sources or verifying data, interpreting and writing history. The approach used is the concept of social history to see how the Dutch East Indies government fortified its people from the threat of plague during the pilgrimage (ḥajj) season. Among the findings of this study is that the Dutch East Indies Government paid special attention to the health management of pilgrims from the East Indies. They conducted regular health checks starting from the port of Tanjung Priok to several places before entering Jeddah. These checks were carried out to prevent the spread of viruses such as cholera, smallpox, and Spanish Flu Abstrak: Artikel ini membahas tentang penanganan kesehatan jemaah haji sejak Ordonantie van 1922, yang mengatur tentang penyelenggaraan ibadah haji di Hindia Belanda. Sebagaimana diketahui, pada masa itu terjadi beberapa wabah penyakit seperti cacar, kolera, dan flu Spanyol. Pemerintah dari seluruh dunia sepakat untuk mencegah penyebaran wabah tersebut dengan melakukan kerja sama di bidang kesehatan. Penelitian ini menggunakan metode penelitian sejarah, yang didasarkan pada empat kegiatan, mulai dari mencari sumber, mengkritik sumber atau memverifikasi data, menafsirkan dan menulis sejarah. Pendekatan yang digunakan adalah konsep sejarah sosial untuk melihat bagaimana pemerintah Hindia Belanda membentengi rakyatnya dari ancaman wabah penyakit pada musim haji. Di antara temuan dari penelitian ini adalah bahwa Pemerintah Hindia Belanda memberikan perhatian khusus terhadap manajemen kesehatan jemaah haji asal Hindia Belanda. Mereka melakukan pemeriksaan kesehatan secara rutin mulai dari pelabuhan Tanjung Priok hingga ke beberapa tempat sebelum memasuki Jeddah. Pemeriksaan ini dilakukan untuk mencegah penyebaran virus seperti kolera, cacar, dan Flu Spanyol.